Monitoring dan Evaluasi Penyelenggaraan Relawan Guru Pendidikan Kristen dan Katolik BKGS Salatiga - Bambang Ismanto; Arief Sadjiarto; Dwi Iga Luhsasi; Lelahester Rina; Destri Sambara Sitorus (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2021)
Primary schools lack Christian and Catholic teachers so there are volunteer teachers of the religious teaching staff. The volunteer has not enough education and teaching experiences. Therefore, provision is important both from a spiritual perspective, introduction to vision and mission, core values of BKGS, and as well as intellectually Christian and Catholic learning methods. The method that we used was to distribute the instrument to partner schools. The activity is carried out in several steps: Preparation, Implementation, Evaluation, and Reporting. The outcome and achievement are the performance of BKGS volunteers who are placed in schools, especially primary school in Salatiga, are classified good. This activity implies that teachers can improve learning strategies in schools through evaluations.